Application of International Relations Theories in Asia and Africa - Grabowski, Marcin (2019)
This book discusses the applicability of Western International Relations (IR) theories to Asia and Africa and the rise of non-Western IR theories (especially in Asia), with case studies focused on the Asia-Pacific, Middle East and Sub-Saharan African regions. Theoretically grounded studies of Asia and Africa are still in high demand, as International Relations scholarship on and in those regions seems underdeveloped in this regard. This is the case both in the application of Western theories in research on Asia and Africa, but especially IR theory-building by scholars in both regions. The book is driven by the question, whether we need specific Asia and Africa-oriented IR theories to describe, explain and predict developments in regional international relations or can we apply or adapt the so-called Western IR theories.